Natural disasters and their influence on the environment - Carrillo Hidalgo, Norma (2001)
Through millions years of earth planet evolution have produced natural phenomenons such as earthquakes, huaycos, floods and many natural phenomenons. Is with the man’s presence that appear the natural disasters and they affect their socio-economic activities and their themselves environment. The natural disasters bring environmental dysfunctions, because they contaminate the soil, water, destroys part of the flora and fauna and almost always create focuses of infections and others, affecting the man’s habitat. In the present work it develops an environmental study of the Cantuta - Chosica area and it culminates with the zoning of risks for effects of the huayco in the study area.